Biosilica-enveloped ferritin cage for more efficient drug deliveries. (May 2018) - Ki, Mi-Ran; Nguyen, Thi Khoa My; Jun, Hyun Sik; Pack, Seung Pil
Graphical abstract: Highlights: Biosilica-enveloped R5-modified ferritin (SiO2 /R5FT) was designed as novel drug carriers. Dox was loaded into interior cage by re-assembly of R5FT and enveloped by R5-mediated biosilicification. Dox loaded in SiO2 /R5FT displayed sustained release, the patterns of which can be controlled by pH (7–5). Abstract: Ferritin (FT), a cage-protein composed of 24 subunits, may carry small molecules inside the core of cage. To enhance the potential of FT as a more functional drug carrier, FT genetically-fused with silaffin R5 peptide at N -terminus (R5FT) and silica-enveloped cage protein (SiO2 /R5FT) were developed. Doxorubicin (Dox) can be loaded into cage interior by re-assembly of R5FT. The release of Dox loaded in internal cages was retarded by the silica-coated matrix and showed the pH-controlled behavior, in which the release amount is larger in acidic environments than neutral. R5FT provides a biocompatible and eco-friendly manufacturing process for the drug-laden silica nanoparticles over conventional production methods.